Piperazine ferulate inhibits diabetic nephropathy by suppressing AGE/RAGE-mediated inflammatory signaling in rats and podocytes - Zhang, Xiu-Meng; Min, Xin-Ran; Xie, Hong-Xiao; Jiang, Yan-Ning; Rui, Yi-Xin; Li, Bo; Zeng, Nan; Liu, Rong (Frontiers in Pharmacology, 2024)
Objective: Diabetic nephropathy (DN) is a serious complication that may occur during the later stages of diabetes, and can be further exacerbated by podocyte damage.Piperazine ferulate (PF) has well-defined nephroprotective effects and is used clinically in the treatment of chronic nephritis and other kidney diseases. However, the renoprotective effects and mechanisms of PF on DN are not clear. This study aims to investigate the protective effect of PF on DN and its mechanism of action, to inform the clinical application of PF in DN treatment. Method: Network pharmacology was performed to predict the mechanism of action of PF in DN. Male Sprague Dawley (SD) rats were intraperitoneally injected with STZ (60 mg/kg) to establish a DN model, and then assessed for renal injury after 12 weeks of administration. In vitro, rat podocytes were treated with 25 mmol/L glucose and cultured for 24 hours, followed by an assessment of cell injury. Results: Our results showed that PF significantly improved renal function, reduced renal pathological changes, decreased inflammatory response, and alleviated podocyte damage in DN rats. PF also attenuated glucoseinduced podocyte injury in vitro. Regarding molecular mechanisms, our study demonstrated that PF down-regulated the expression of genes and proteins related to AGE-RAGE-mediated inflammatory signaling. Conclusion: In summary, PF exerts its renoprotective effects by decreasing inflammation and protecting against podocyte injury through the inhibition of the AGE/RAGE/NF-κB/NLRP3 pathway. Overall, these data support the clinical potential of PF as a renoprotective agent in DN.